The Impact of Project-Based Learning on Students' Collaboration Skills in Secondary Schools - Mustamin, Kaso; Wahdah, Wahdah; Intiardy, Dermawan; Jumrah, Abrina Maulidnawati; Pattiasina, Petrus Jacob (International Journal of Educational Research Excellence (IJERE), 2024)
The objective of this study was to investigate the influence of project-based learning (PBL) on students' collaborative abilities within the context of secondary education. The investigation encompassed three key areas: communication, teamwork, and collaborative problem-solving.The research employed a qualitative methodology with a case study approach. Data were collected through in-depth interviews, observations, and document analysis of students and teachers. The findings indicated that PBL markedly enhanced students' collaborative abilities, particularly in the domains of communication, teamwork, and problem-solving. However, certain obstacles emerged, including time management and the necessity for more efficacious teacher roles as facilitators.In conclusion, the findings of this study indicate that project-based learning (PBL) has a significant impact on students' collaboration skills, particularly in terms of communication, teamwork, and problem-solving abilities. However, the implementation of PBL in secondary education contexts is not without challenges, including the need for effective time management strategies and the strengthening of teachers' capacity as facilitators. PBL is an effective method for enhancing students' collaborative abilities. However, its implementation necessitates the provision of adequate support in the form of effective time management strategies and the enhancement of teachers' capacity to serve as effective facilitators.